Studi komparasi Undang-undang perkawinan No. 1 Tahun 1974dan imam madzhab tentang wali adhol - Shobur, Mufidus; Irawan, Ah. Soni (AS-SAKINAH, 2023)
Wali adhol is a guardian who is reluctant to marry a woman who has reached puberty and has the right mind with a man of his choice even though each prospective bride wants her marriage to take place immediately. This research has two discussions, First: The nature of wali adhol according to Marriage Law Number 1 of 1974 and the opinion of the madzhab imams. Second: How is the law of wali adhol according to Marriage Law Number 1 of 1974 and the opinions of the madzhab imams. The results of this study can be concluded that Marriage Law Number 1 of 1974 is in line with the opinion of the majority of scholars, namely if the nasab guardian is adhol for reasons that are not shar'i or reasons that are not based on Islamic law, then the marriage of the bride-to-be using a judge's guardian is legal, considering that in the view of the Shafi'i madzhab and the majority of scholars state that the judge's guardian can function as a substitute for the nasab guardian and his status is not a representative of the nasab guardian due to emergency reasons.